2022
DOI: 10.1161/circinterventions.122.011848
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Gastrointestinal Bleeding in Patients With Heyde Syndrome Undergoing Transcatheter Aortic Valve Implantation

Abstract: Background: Heyde syndrome is the co-occurrence of aortic stenosis and gastrointestinal bleeding secondary to angiodysplasias. Surgical aortic valve replacement effectively reduces bleeding, but the effects of transcatheter aortic valve implantation (TAVI) are largely unknown. This study aimed to describe the reduction of gastrointestinal bleeding in patients with Heyde syndrome after TAVI and to identify the factors associated with rebleeding. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Recurrence of gastrointestinal bleeding is probably related to residual para-valvular regurgitation. 9 , 10 In contrast, angiodysplasia remains visible on endoscopy without the development of gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of gastrointestinal bleeding is probably related to residual para-valvular regurgitation. 9 , 10 In contrast, angiodysplasia remains visible on endoscopy without the development of gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current HS patients were elderly and had severe AS with many underlying diseases and bleeding tendencies, rendering tolerance of surgery low and informing a choice of TAVI. Goltstein et al ahve rpeviosuly shown that 62% of TAVI-treated HS patients had complete resolution of GIB in the first year after surgery and 83% did not have further GIB during the 5-year follow-up [ [ 42 ] ] . The current findings are in line with previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently identified PVR as risk factor for recurrence of gastrointestinal bleeding after TAVR in patients with Heyde syndrome, further stressing the need for reduction of PVR. 28 Thus, assessment of PVR, including the use of the correct parameters and/or adoption of sensitive cut-offs, is of utmost importance in determining prognosis. Also, it could guide additional therapies aiming to reduce PVR and improve clinical outcome after TAVR.…”
Section: Discussionmentioning
confidence: 99%